Pengembangan Media Komik Terintegrasi Budaya Lokal Tumpek Wariga sebagai Upaya Peningkatan Kepedulian terhadap Lingkungan pada Anak Usia Dini - Putu Eka Sastrika Ayu; Ni Luh Ika Windayani (Universitas Pendidikan Ganesha, 2023)
Growing a caring attitude is carried out during the learning process by using media in comics that are integrated with the local culture of tumpek wariga. This research aims to test the effectiveness of the local culture-integrated comic media tumpek wariga to increase awareness of the environment in early childhood. This research belongs to the type of development research using the 4-D development model. The subjects in this study were two education experts, two practitioners, six lecturers, 40 teachers, and 30 early childhood children. Data collection uses a non-test method with a research instrument in the form of a questionnaire. The data obtained in the study were then analyzed by construct validity test using the Gregory formula. Comic effectiveness data is measured based on the achievement of comic goals that have been developed, using a one-variable t-test formula with one right-side direction. The data analysis results show that expert validation results are valid. The practicality of comic media due to the lecturer's response to the implementation of comics is very practical in affective aspects, interactive aspects, interesting, efficient, and creative. The results of the teacher's response to the module's implementation are practical in the effective, interactive, interesting, efficient, and creative aspects. Applying local culture-integrated comics, tumpek wariga affects children's concern for the environment. Based on these results, it can be concluded that applying local culture-integrated comics, tumpek wariga, increases children's concern for the environment.